Prevalence and predictors of suicidal-risk behaviors among Paraguayan in-school adolescents: A sex-stratified analysis - Taufique Ahmed; Tanjin Kabir Aunto; Md. Khalid Hasan (Current Research in Behavioral Sciences)
This study performs a sex-stratified analysis of the prevalence and predictors of suicidal risk behaviors (SRBs) among Paraguayan adolescents, utilizing data from the 2017 Global School-based Student Health Survey (GSHS). The study’s participants comprised a sample of 3149 school-attending adolescents, of whom 51.2% were female. Multiple logistic regression analyses were used to investigate the risks and protective factors influencing suicidal-risk behaviors. The prevalences of suicidal ideation, suicidal plan, suicidal attempt, and any suicide-risk behavior were 13.8%, 13.3%, 11.2%, and 19.3%, respectively, and significantly higher among girls (suicidal ideation 9.3%, suicidal plan 8.3%, suicidal attempt 6.9%, and any suicide-risk behavior 12.1%) than boys. According to sex-stratified analysis, there are several risk factors identified for suicidal-risk behaviors among girls, including anxiety, loneliness, lack of a close friend, physical attack, injury, current drinking alcohol, and sedentary behavior. In contrast, bullying and fighting were more significantly associated factors with boys’ suicidal-risk behaviors. We found lower associations with SRBs among Paraguayan in-school adolescents, who reported higher parental supervision and regular homework checking. This study identified significant sex differences in suicidal-risk behaviors. Our study highlights a requirement for early screening programs and interventions aimed at high-risk adolescents in Paraguay to lower the risk of SRBs among this population.